Telomere-to-telomere gapless genome assembly of Triplophysa yaopeizhii - Li Ma; Xu Zeng; Jixiao Wang; Hao Xiong; Yongyao Yu; Haiping Liu; Qing-Yong Yang; Ruibin Yang; Xuefen Yang (Scientific Data)
Abstract The genus Triplophysa exhibits remarkable adaptability to the unique environment found at the Qinghai-Tibet Plateau (QTP). Higher quality genomes are helpful to the study of the adaptability to the extreme environment in the plateau. This study utilized PacBio HiFi, Ultra-long ONT, and Hi-C sequencing of Triplophysa yaopeizhii to construct the first telomere-to-telomere (T2T) gapless genome assembly of the genus Triplophysa. The genome size is 671.58 Mb, with a contig N50 length of 26.04 Mb. The sequences were anchored onto 25 chromosomes with all centromeres and telomeres. Furthermore, 293.98 Mb (43.77%) of repetitive sequences and 26,487 protein-coding genes were identified. Comparative analyses with the genomes of closely related species demonstrated high completeness, continuity, and accuracy of the genome. The genomic quality was further substantiated by the QV of 31.82 with 96.60% of BUSCO. This study provides a valuable genetic resource of the genus Triplophysa and serves as an essential reference for elucidating the adaptive genetic mechanisms of plateau fish to the high altitude.